1999
DOI: 10.1177/155005949903000110
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Caffeine Withdrawal on Cognitive P300 Auditory and Visual Evoked Potentials

Abstract: Auditory and visual P300 cognitive evoked potentials were obtained in 13 individuals who regularly consumed caffeine prior to and during a 4 day period of abstinence from caffeine. During the period of caffeine abstinence auditory P300 evoked potentials showed significant decreases in amplitude measures but no significant changes in latency, while the visual P300 evoked potentials showed significant latency decreases but no significant changes in amplitude. The reason for these opposite effects is unclear and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Other studies that have analyzed the interaction between ERPs and caffeine are not conclusive. Some studies indicate a shortening of latency (17,18,(29)(30)(31), while others show an increase in amplitude (28,32). However, the use of different experimental conditions makes it impossible to compare the results.…”
Section: Cognitive and Motor Measuresmentioning
confidence: 96%
See 1 more Smart Citation
“…Other studies that have analyzed the interaction between ERPs and caffeine are not conclusive. Some studies indicate a shortening of latency (17,18,(29)(30)(31), while others show an increase in amplitude (28,32). However, the use of different experimental conditions makes it impossible to compare the results.…”
Section: Cognitive and Motor Measuresmentioning
confidence: 96%
“…Few ERP experiments have attempted to correlate the modulatory effects of caffeine on cognitive processes, attention and arousal in terms of P300 amplitude and latency (16,(29)(30)(31)(32). A combination of peripheral behavioral responses such as reaction time and attention together with central electrophysiological responses may contribute to the understanding of caffeine's mechanisms of action.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the experimental conditions, caffeine ingestion will produce different effects on P300 latency. Reeves et al 19 observed a shortening of P300 latency but no changes in P300 amplitude with 13 caffeine-user subjects, submitted to four days of caffeine-deprivation. Recently, investigators observed hypo- glycemia in normal 26 and diabetic 13 subjects through changes in P300 outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…Caffeine's behavioral effects have been documented in a number of laboratories, as well as improvements on attention, mood and vigor tasks. Moreover, a decrease on reaction time and changes on P300 latency 15,19 and amplitude 18 have been associated with the modulator effects of caffeine. Nevertheless, worldwide labs have presented contradictory results and different experimental procedures.…”
mentioning
confidence: 99%
“…In this context, caffeine can be regarded as a neuromotor modulator. More o v e r, a decrease on reaction time and changes o n P300 latency 11,12 and amplitude 13 have been associated with caff e i n e 's modulatory effects. In a rec e n t s t u d y, a shorter P300 latency and higher amplitude, specifically at Fz, were observed after the administration of caffeine when compared to placebo.…”
Section: Snc) O B J E T I V Omentioning
confidence: 99%